Municipal transparency and social control: the Social Observatories’ view on transparency portals and access to information - Di Marco, Cláudio Augusto Ferreira (2022)
The article analyzes the innovations introduced in the publicity of actions and result of public management through the portals of transparency and access to information, verifying their effectiveness in facilitating social control, seeking to indirectly assess the opinion of users on the quality of portals created to meet the requirements of the Transparency Law (LT) and the Law on Access to Information (LAI) of municipalities, collecting data with the heads of entities of the Brazil's Social Observatory network found within a sample representing 6.7% of the state's cities, but comprising more than 20 million inhabitants. The research indicated that the transparency portals have been an important informational environment for the entities but need improvements, especially considering the unfriendly access and the difficulties in finding the information, as well as getting adequate responses to the requests. As a suggestion for improvement, it is recommended the creation of participatory evaluation mechanisms, such as transparency councils and social control.